2022
DOI: 10.1002/acr.24809
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Early Knee Osteoarthritis Illness Among Various Patient‐Reported Classification Criteria After Anterior Cruciate Ligament Reconstruction

Abstract: Objective. To compare the prevalence of participants meeting different patient-reported criteria for early osteoarthritis (OA) illness after anterior cruciate ligament reconstruction (ACLR).Methods. Participants completed the Knee Injury and Osteoarthritis Outcomes Score (KOOS) at a single time point 5.0-7.9 months post-ACLR. We used established KOOS subscale criteria (i.e., Luyten original and Englund original) to define patient-reported early OA illness. A two-by-two contingency table and McNemar's test were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Our novel findings identify early deficits in knee-related QOL of youth with a broad range of knee injuries compared with uninjured peers. At 6 months post-ACLR, youth have reported KOOS QOL scores (mean range 56-68), 3,4,33,34 but only one of these studies compared knee-related QOL between youth with and without an ACL rupture and found deficits. 3 Given that long-term impairments in knee-related QOL are common, 1,35,36 these early deficits should be addressed immediately after a knee injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our novel findings identify early deficits in knee-related QOL of youth with a broad range of knee injuries compared with uninjured peers. At 6 months post-ACLR, youth have reported KOOS QOL scores (mean range 56-68), 3,4,33,34 but only one of these studies compared knee-related QOL between youth with and without an ACL rupture and found deficits. 3 Given that long-term impairments in knee-related QOL are common, 1,35,36 these early deficits should be addressed immediately after a knee injury.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we have applied dualMRI and qMRI techniques in a clinical cohort of patients six months post-ACLR to determine which MRI metrics may best predict patient-reported outcomes. While previous work has quantified macro-scale whole joint mechanical changes post ACLR 3,18,21,50 , to our knowledge, this is the first study that has quantified cartilage tissue-level (i.e., intratissue) mechanical changes in this clinical population. This study had two objectives: first, we evaluated the extent that dualMRI and qMRI metrics are associated with knee function and pain at six-months post-ACLR, as assessed by standardized patient-reported outcome scores 16,41 .…”
Section: Introductionmentioning
confidence: 99%
“…10 The Englund classification has also been applied to patients early after ACLR. 11,12 Recent investigations have explored the relationship between symptomatic knees and clinical outcomes, 12 and explored the utilization of these criteria in patients approximately 6-months post-ACLR. 11 However, to the authors' knowledge, there is limited evidence that has explored the relationship between osteoarthritis symptomology, health-related quality of life and psychological outcomes in people with a history of ACLR.…”
Section: Introductionmentioning
confidence: 99%